1999
DOI: 10.1590/s0001-37141999000300016
|View full text |Cite
|
Sign up to set email alerts
|

Hepatosplenomegaly caused by an extract of cyanobacterium Microcystis aeruginosa bloom collected in the Manguaba Lagoon, Alagoas - Brazil

Abstract: Cyanobacteria (Microcystis aeruginosa), which produce powerful hepatotoxic cyclopeptides, were collected and submitted to the determination of toxicity through intraperitoneal injections made in 30 and 90 days-old Swiss albino mice. The liver and the spleen were histopathologically analyzed and the weight and vital signs development were monitored. Test of toxicity resulted in a LD 50 of 154.28 mg.Kg -1 . M. aeruginosa represented 95% of the analyzed biomass. The ratios between liver weight and body weight in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…According to Lawton et al (1994) classification, this bloom presented low toxicity; in general, the LD 50 toxicity values of Brazilian natural blooms containing microcystins ranged from 35.5 to 445.45 mg.kg -1 (25,29,33,40,47) and can be classified among the most toxic blooms. For the isolated strains of microcystin producers, the lowest LD 50 value is 13.7 mg.kg (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…According to Lawton et al (1994) classification, this bloom presented low toxicity; in general, the LD 50 toxicity values of Brazilian natural blooms containing microcystins ranged from 35.5 to 445.45 mg.kg -1 (25,29,33,40,47) and can be classified among the most toxic blooms. For the isolated strains of microcystin producers, the lowest LD 50 value is 13.7 mg.kg (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…In Brazil, where these events are very frequent, the most common freshwater bloom forming genera are Microcystis, Anabaena, Aphanizomenon, Planktothrix, and Cylindrospermopsis, which is also the most studied cyanobacterial group (3,6,18,24,28,33,38,40,43,47).…”
Section: Introductionmentioning
confidence: 99%
“…The neurotoxins (anatoxin-a, homoanatoxin-a, anatoxin-a(s), saxitoxin and neosaxitoxin) act on the central nervous system, working as muscle blockers, and causing death by respiratory failure. The hepatotoxins include microcistins, nodularins and cilindrospermopsins, which produce symptoms such as weakness, paleness, cold extremities, breathlessness, vomiting and diarrhea, and can also cause death by respiratory failure, hepatic hemorrhage, and in some cases tumor apparition (Carmichael, 1994;Watanabe et al, 1996;Porfirio et al, 1999;Codd, 2000;Falconer, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The commonly encountered toxin producing species of cyanobacteria include Anabaena circinalis, Aphanizomenon flos-aquae, Microcystis aeruginosa, and Cylindrospermopsis raciborskii (Azevedo et al, 1994;Lagos et al, 1999). In Brazil, the toxic blooms of the cyanobacteria have been reported in the coastal lagoons (Azevedo, 1994;Porfirio et al, 1999;Magalhães et al, 2001;Lagos et al, 1999), in the estuaries (Matthiensen et al, 1999), and in the reservoirs (Bouvy et al, 2000;Chellappa et al, 2000). It has been reported that the presence of the microcystin toxin from the blooms of Microcystics aeroginosa in the water storage tank of a haemodialysis clinic resulted 53 deaths in Caruaru city, in the state of Pernambuco (Jochimson et al, 1998).…”
Section: Introductionmentioning
confidence: 99%